Peran Perguruan Tinggi Keagamaan dalam Penguatan Moderasi Beragama: Strategi, Kebijakan, dan Implementasi di Jawa Timur - Budi, Budi Ichwayudi; Nasich, Ah. Nasich Hidayatulloh (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
Religious moderation has become a significant concern, especially after the government designated it as a national program, including within the academic community in higher education institutions in East Java. This study aims to examine the strategies, policies, and implementation of religious higher education institutions in strengthening religious moderation in the region. Employing a qualitative approach, this research focuses on three religious higher education institutions and utilizes the Miles and Huberman model for data analysis. The study maps the extent of policies and their implementation to assess the role of religious higher education in reinforcing religious moderation. The findings indicate that the policies and strategic directions for strengthening religious moderation in these institutions align with their respective institutional roadmaps. This alignment is evident in curriculum content, research, and community service programs. The study contributes to the discourse on religious moderation by highlighting the role of higher education institutions in shaping and implementing relevant policies.